Intelegensi dan Multiple Inteligensi - Nehru Meha (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Essentially all children are smart, and intelligence of every child is different, parents and teachers only need to provide the right environment to deliver the full potential of intelligence. In the early childhood education, parent and teacher is not teaching, but are stimulating the child to their own intelligence, resulting in the child-centered learning. Stimulation can be provided by way of giving children the opportunity to become intelligent and creative. Allow the child to freely make, hold, draw, shape, or make the child’s own way and describe his own experience. When children develop imagination and intelligence, then they also can generate innovative ideas and way out in resolving the problem. One way that could turn creativity sparks of early childhood is to liberate the child to pours his thoughts. Keywords: Intelligence, Multiple Intelligence, Intelligence Development, and Intelligence Test.